Policies in support of pastoralism and biodiversity in the heterogeneous drylands of East Africa - Notenbaert, An Maria Omer; Davies, J.; Leeuw, Jan de; Said, Mohammed Yahya; Herrero, Mario; Manzano, P.; Waithaka, M.M.; Aboud, A.A.O.; Omondi, S. (Springer, 2012)
Research and practice are increasingly demonstrating the environmental benefits of pastoralism and the opportunity for sustainable development of pastoral communities through a combination of livestock and biodiversity-related business. To take full advantage of the potential biodiversity-pastoral synergies, it will be crucial to put in place supporting policies. They need to be embedded in the context of overall pastoral development. However, rangelands and pastoral societies in drylands are heterogeneous and development options cannot be assumed to be uniform. Factors such as aridity, access to markets and population pressure influence the constraints and the opportunities for both pastoral and non-pastoral communities. We describe the differential challenges to development along these gradients and identify investment priorities if the policy objectives were to support the complementarities between pastoralism and biodiversity conservation.